Radiographic imaging for the dental team - Miles, Dale A. (St. Louis, Mo. : Saunders Elsevier, 2009)
From the Publisher: Fully revised and up to date, the 4th edition of this trusted, all-in-one work-text helps you effectively acquire, process, and review dental radiographs and ensure successful patient outcomes. Learn and apply essential imaging techniques with ease while staying up-to-date on the latest technology and the most current practices in dental radiography. Concise, easy-to-read chapters detail the complete spectrum of radiographic imaging, supported by valuable review material to help you solidify your understanding of key concepts and prepare for professional success! Study questions at the end of each chapter help you assess your knowledge and identify areas requiring further review. Glossary of radiographic terms presents essential terms and definitions in one convenient place. Updated photographs and illustrations reflect the most current tools and technology in the field. Chapter on implant and extraoral imaging helps you better understand the link between these two related techniques and ensure the most accurate image evaluation. Design and chapter organization make content more accessible and inviting. Companion Evolve website reinforces your understanding with review activities and practice exams
1: Intraoral Radiographic Technique -- Before you begin -- Intraoral radiographic techniques -- Types of radiographic surveys -- Intraoral radiography: basic principles -- Paralleling technique -- Helpful hints for intraoral imaging -- Infection control -- 2: Image Processing And Quality Assurance -- Film composition -- Film speed -- Latent image formation -- Concepts of film processing -- Technical aspects of film processing -- Chemical composition of solutions -- Care of solutions -- Darkroom -- Automatic film processing -- Troubleshooting: diagnosing processing errors -- Mounting films -- Duplicating films -- Infection control for processing films or phosphor plates -- 3: Film Mounting And Normal Radiographic Anatomy -- Mounting dental radiographs -- Teeth and adjacent structures -- Maxillary and mandibular anatomic landmarks -- 4: X-Ray Properties And The Generation Of X Rays -- Discovery of X Rays -- Properties of X Rays -- Components of a dental X-Ray tube -- Production of X Rays -- 5: Radiation Biology And Protection -- Effects of radiation on molecules -- Effects of radiation on cells -- Units of radiation measurement -- Amounts of radiation used in dental radiography -- Risk versus benefit of dental radiographic images -- Radiation protection for the patient -- Radiation protection for the operator -- Risk management and dental imaging -- 6: Image Characteristics -- Visual qualities of an X-Ray image -- Geometric characteristics -- 7: Digital imaging -- What is a digital image? -- Types of digital imaging systems -- Digital image processing -- Digital image properties -- Digital imaging applications -- 8: Panoramic Imaging -- Equipment for film-based extraoral imaging -- Equipment for direct digital panoramic imaging -- Panoramic imaging principles -- Cone beam panoramic projections -- 9: Trouble-Shooting Technique And Processing Errors -- Errors in exposure technique -- Processing errors -- Additional miscellaneous errors -- 10: Accessory Radiographic Techniques And Patient Management -- Bisecting-angle technique -- Occlusal imaging -- Pediatric imaging techniques -- Edentulous radiographic techniques -- Endodontic imaging techniques -- Localization techniques -- Patient management -- Patients with disabilities -- Anatomic considerations -- 11: Extraoral, Specialized, And Implant Imaging -- Lateral oblique jaw projections -- Cephalometric projections -- Temporomandibular joint views -- Maxillary sinuses -- Implants -- 12: Basics Of Interpretation: Normal Versus Abnormal And Common Radiographic Presentation Of Lesions -- Detection of disease or other abnormal conditions -- Basic viewing principles -- Describing abnormal conditions -- Interpretation of abnormalities -- Radiographic changes resulting from dental caries -- Radiographic changes resulting from periodontal disease -- Radiographic changes resulting from periapical infection -- Radiographic changes resulting from trauma -- Radiographic features of dental anomalies -- Radiographic signs of disease -- Glossary of radiologic terms
Includes bibliographical references and index
Keywords: Teeth -- Radiography; Dental auxiliary personnel; Radiography, Dental -- methods; Dental Auxiliaries